POTENSI ANTIDIABETES DAUN Smallanthus sonchifolius : A SYSTEMATIC LITERATURE REVIEW TERHADAP MEKANISME MOLEKULER DAN BUKTI IN VITRO SERTA IN VIVO - Elisa Issusilaningtyas; Septiana Indratmoko; Rianatul Chasanah; Tatang Tajudin; Rizki Azmi Nurmajid (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Diabetes mellitus is a chronic metabolic disease with an increasing global prevalence and remains a major cause of microvascular and macrovascular complications. Plant-derived antidiabetic agents have attracted considerable attention due to their therapeutic potential and relatively low adverse effects.Yakon (Smallanthus sonchifolius) leaves contain numerous bioactive compounds that may regulate glucose homeostasis through multiple molecular pathways. This study systematically reviewed the available scientific evidence regarding the antidiabetic activity of Smallanthus sonchifoliusleaves based on in vitro and in vivo studies. A Systematic Literature Review was conducted following PRISMA 2020 guidelines. Literature searches were performed in the Scopus database using the keywords